CPT(®) Codes: What Are They, Why Are They Necessary, and How Are They Developed? - Dotson, Peggy (Mary Ann Liebert, Inc., 2013)
Qualified healthcare professionals (QHPs) need to identify the professional services they provide and to report those services in a way that can be universally understood by institutions, private and government payers, researchers, and others interested parties. The QHPs' data are used to track healthcare utilization, identify services for payment, and to gather statistical healthcare information about populations. Each year, in the United States, healthcare insurers process over 5 billion claims for payment.(1) To ensure that healthcare data are captured accurately and consistently and that health claims are processed properly for Medicare, Medicaid, and other health programs, a standardized coding system for medical services and procedures is essential. The Current Procedural Terminology (CPT(®)) system, developed by the American Medical Association (AMA), is used for just these purposes. The AMA system provides a standard language and numerical coding methodology to accurately communicate across many stakeholders, including patients, the medical, surgical, diagnostic, and therapeutic services provided by QHPs. The CPT descriptive terminology and associated code numbers provide the most widely accepted medical nomenclature used to report medical procedures and services for processing claims, conducting research, evaluating healthcare utilization, and developing medical guidelines and other forms of healthcare documentation.